Variation in Ecophysiological Traits and Drought Tolerance of Beech (Fagus sylvatica L.) Seedlings from Different Populations - Cocozza, Claudia; de Miguel, Marina; Pšidová, Eva; Ditmarová, L'ubica; Marino, Stefano; Maiuro, Lucia; Alvino, Arturo; Czajkowski, Tomasz; Bolte, Andreas; Tognetti, Roberto (Frontiers in Plant Science, 2016)
Frequency and intensity of heat waves and drought events are expected to increase in Europe due to climate change. European beech (Fagus sylvatica L.) is one of the most important native tree species in Europe. Beech populations originating throughout its native range were selected for common-garden experiments with the aim to determine whether there are functional variations in drought stress responses among different populations. One-year old seedlings from four to seven beech populations were grown and drought-treated in a greenhouse, replicating the experiment at two contrasting sites, in Italy (Mediterranean mountains) and Germany (Central European). Experimental findings indicated that: 1) drought (water stress) mainly affects gas exchange describing a critical threshold of drought response between 30 and 26% SWA for photosynthetic rate and Ci/Ca, respectively; 2) the Ci to Ca ratio increases substantially with severe water stress suggesting a stable instantaneous water use efficiency and an efficient regulation capacity of water balance achieved by a tight stomatal control; 3) there was a different response to water stress among the considered beech populations, differently combining traits, although there was not a well defined variability in drought tolerance. A combined analysis of functional and structural traits for detecting stress signals in beech seedlings is suggested to assess plant performance under limiting moisture conditions and, consequently, to estimate evolutionary potential of beech under a changing environmental scenario.